2015
DOI: 10.1109/jphotov.2014.2361014
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Redesigned, High-Radiative-Efficiency GaInP Junctions on III-V Multijunction Concentrator Solar Cells

Abstract: Abstract-Nonradiative recombination in inverted GalnP junctions is dramatically reduced using a rear-heterojunction design rather than the more traditional thin-emitter homojunction design. When this GalnP junction design is included in inverted multijunction solar cells, the high radiative efficiency translates into both higher subcell voltage and high luminescence coupling to underlying subcells, both of which contribute to improved performance. Subcell voltages within two and four junction devices are measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Fig. 2 shows the emission spectra along with the EQE of a twojunction GalnP/GaAs tandem solar cell in which both junctions are rear-heterojunction devices which have been shown to have high radiative emission [19,20]. In the bottom-junction limited case (top cell over-illuminated), the bottom junction is reverse biased and gives no EL emission, but there is still measurable luminescence around the bandgap wavelength which is hence identified as the short-circuit PL contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2 shows the emission spectra along with the EQE of a twojunction GalnP/GaAs tandem solar cell in which both junctions are rear-heterojunction devices which have been shown to have high radiative emission [19,20]. In the bottom-junction limited case (top cell over-illuminated), the bottom junction is reverse biased and gives no EL emission, but there is still measurable luminescence around the bandgap wavelength which is hence identified as the short-circuit PL contribution.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that V oc can approach the value predicted in the internal radiative limit. However, the trueηitalicint¯ at the maximum power point (MPP), where J rec is smaller than J sc , is generally lower than that at the OC condition . These results evidence that there is room for reduction of non‐radiative recombination losses at the MPP.…”
Section: Introductionmentioning
confidence: 93%
“…Since it is difficult to completely eliminate the optical losses, which depend on the device geometry, η int is usually used for solar cell analyses. The average η int of the total junction volume ( trueηitalicint¯) depends on the recombination current density ( J rec ), and trueηitalicint¯ generally increases with J rec . Previous studies have shown that a trueηitalicint¯ close to 100% can be realized in the case that J rec equals the short‐circuit current density ( J sc ), i.e., it can be realized at the open‐circuit (OC) condition with output voltage V oc .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the frontcontact resistance and top cell sheet resistance limit the performance, as determined from transmission-line measurements. However, the sheet resistance of the top cell has been reduced from 400 to 100 Q/D by using a rear-heterojunction design with a thick emitter layer rather than a traditional front-homojunction design [8], [20]. The rear-heterojunction structure allows the full thickness of the top cell to transport carriers laterally.…”
Section: A Concentration Performancementioning
confidence: 99%